2021
DOI: 10.1016/j.jhin.2021.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a SARS-CoV-2 infection prevention model in elective surgery patients – a prospective study: does universal screening make sense?

Abstract: On behalf of COVID19-ALC research group, Effectiveness of a SARS-CoV-2 infection-prevention model in elective surgery patients, a prospective study: Does Universal Screening Make Sense?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In fact, in the same period in our hospital, patients who underwent surgery were screened for COVID-19 with universal preprocedural PCR and the incidence of a positive test was 0.0022 among asymptomatic patients. No healthcare workers-associated infections were detected [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in the same period in our hospital, patients who underwent surgery were screened for COVID-19 with universal preprocedural PCR and the incidence of a positive test was 0.0022 among asymptomatic patients. No healthcare workers-associated infections were detected [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Screening procedures will, and already have, become less involved, with many institutions no longer requiring PCR testing and only relying on symptom screening. A selective rather than universal approach to PCR testing prior to elective surgery has been shown to be safe ( 72 ). The role of antigen testing is unclear although has been proposed ( 73 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patient may be asymptomatically, or more notably, pre-symptomatically infected with SARS-CoV-2 at the time of a surgical procedure 1 , potentially increasing the risk of both post-procedural mortality 2,3 and the risk of transmission. Previous studies found that that the utilization of preoperative testing may be beneficial in certain settings [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%